FORMATION AND DEVELOPMENT OF VERTISOLS IN SELIVANY PLAIN AT DUHOK GOVERNORATE, KURDISTAN REGION, IRAQ - ABDULRAHMAN, HALIZ DARWISH; FAYYADH, MOHAMMED ALI; DOSKI, JAMAL A.H. (Journal of Duhok University, 2020)
The study area located at the Selivany plain in Duhok governorate, Kurdistan Region, Iraq. Forty- three soil samples were taken from horizons in all studied pedons then physically and chemically analyzed according to standard methods. The studied soils were slightly alkaline non- saline. The values of CEC increased with increasing clay content. The Studied soils considered Vertisols and occurs pedoturbation, in turn, trans-locating organic matter from surface to subsurface and deep horizons, additionally, existing plant roots contribute in increasing organic matter in these horizons, and the humification process can occur in different soil horizons. Total carbonate content increased with increasing depth in subsurface horizons this due to the origin of limestone parent materials. The differences in carbonate distribution manner indicated to development. The studied soils contain a considerable amount of active carbonate that affecting different soil properties. Relatively high clay content in studied soils and its content at the surface horizons are lower than it at subsurface horizons. The high value of clay and silt content indicates to soil development. The following pedogenic processes can be specified loss, gain, leaching, illuviation, eluviation, alkalization, humification, lessivage, desalinization, calcification, decomposition, synthesis, pedoturbation, and braunification. Humification processes of organic matter are predominate because the ratio of carbon to nitrogen (C / N) is less than 25. According to the criterion (Total clay in B-horizon / Total clay at A-orizon) most of the studied pedons (1, 3, 6, 7, 8, 9, 10, 12, 13, and 14) considered as well developed soils. The ratio of (Active carbonate/ Total carbonate) was high ranged between (0.31-3.14%), and this may be due to the high weathering intensity of parent material, as a result of increased the ratio mass of active carbonate to total carbonate.